The Origins and Values of Javanese Philosophy in Nyadran with Goat-Cow Slaughter - Sartini, Sartini; Luwiyanto, Luwiyanto; Rr Yudiswara, Permatasari Ayu; Nur, Fitri Amalia (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2024)
This research aims to explore the origins of Nyadran, focusing on its ritualistic aspect involving the use of large animal parts (cows or goats), and to elucidate the underlying philosophy. Utilizing qualitative data from literature reviews and field studies, interviews were conducted to understand community perspectives. Findings reveal that Nyadran's implementation, involving slaughtering animals, lacks direct links to Islamic teachings and shows no explicit involvement of Islamic figures from the past. Instead, Nyadran's concepts stem from myths surrounding the village or the region in which it is organized. Community knowledge is grounded in beliefs about intertwined historical events and evolves with the growth of religious institutions. Justifications for Nyadran are based on philosophical arguments of religious, moral, and societal values, supporting the need for strong communal values and a harmonious life.